2019
DOI: 10.1108/prt-08-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline-based curcumin extraction from selected zingiberaceae for antimicrobial and antioxidant activities

Abstract: Purpose The purpose of this paper is to extract, characterise and quantify curcumin from selected Zingiberaceae of “kunyit” or turmeric (Curcuma longa), “temu lawak” or Javanese turmeric (Curcuma xanthorrhiza), “temu pauh” (Curcuma mangga), “lempoyang” (Zingiber zerumbet) and “bonglai” (Zingiber cassumunar) using alkaline and chemical-based extraction method for antimicrobial and antioxidant activities. Design/methodology/approach Through the alkaline-based extraction method, all parts of rhizome samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Apart from its characteristic complex flavor, it is also appreciated as a colorant providing a yellow hue to the dishes [2]. Besides, turmeric is rich in active components with antibacterial, anti-inflammatory, anti-diabetic and antioxidant activities so it has been used in traditional Asian medicine as well [3][4][5][6]. Among other components, phenolic compounds, curcumin and related species have been found to be responsible for those beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its characteristic complex flavor, it is also appreciated as a colorant providing a yellow hue to the dishes [2]. Besides, turmeric is rich in active components with antibacterial, anti-inflammatory, anti-diabetic and antioxidant activities so it has been used in traditional Asian medicine as well [3][4][5][6]. Among other components, phenolic compounds, curcumin and related species have been found to be responsible for those beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric’s effects on health in general are centered on an orange-yellow lipophilic polyphenol called “curcumin,” which is obtained from the roots of the herbs (Ibáñez and Blázquez, 2021; Hosseini and Hosseinzadeh, 2018). Recently, curcumin has been known to have antioxidant, anti-inflammatory, antimicrobial and anticancer effects, wound healing property and gastroprotective activities (Othman et al , 2019; Hosseinzadeh et al , 2017; Jia et al , 2021). One environmentally friendly inhibitor that is rarely investigated is turmeric extract which can be used as a preferred alternative to inhibitors of organic chemicals such as azole derivatives and others.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are also associated with another associated surgery for taking out the implant and increasing the overall cost of the medical operation for the patient. To avoid this kind of situation, magnesium and its alloys come into the picture, which is known for their excellent biocompatibility and are also a bioresorbable material, thereby eliminating the need for a second surgery, and is also an attractive biomaterial owing to its light weight, low stress-shielding effect because of similar modulus of magnesium alloys (∼45 GPa) with that of human bone (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), the similarity of density to that of cortical bone, while also being an essential mineral for metabolism in humans [1,2]. However, it has to be kept in mind that magnesium is corrosive even in physiological pH (7.4-7.6).…”
Section: Introductionmentioning
confidence: 99%
“…It is, thus, used in coating food items to improve their antimicrobial efficacy and inhibit bacterial contamination due to the presence of an inherent orange-yellow lipophilic polyphenol compound named 'curcumin'. Recent studies on curcumin showed that in addition to anti-microbial properties, it also has antioxidant, anti-inflammatory, anti-cancer and wound healing properties [20][21][22][23]. Turmeric is also used in preparing foods because of its powerful anti-inflammatory properties, thus making it a suitable candidate for biomedical applications [24,25].…”
Section: Introductionmentioning
confidence: 99%